Code Switching in the Things Left Behind Novel By Kim Sae Byoul and Jeon Ae Won - Gede Kediri Suryadharma, Gede Kediri Suryadharma (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
Code switching is a prevalent sociolinguistic phenomenon observed in various communication settings, including literary works. This study explores the occurrence of code switching in the novel "Things Left Behind" by Kim SaeByoul and Jeon Ae Won. The research adopts a descriptive qualitative approach, utilizing Charlotte Hoffmann's theory to analyze the types and functions of code switching found in the novel. The data source comprises the text of "Things Left Behind," allowing for a comprehensive examination of language usage within the narrative. The study identifies three types of code switching present in the novel, namely inter-sentential switching, intra-sentential switching, and tag switching. Through careful analysis, it is revealed that code switching is purpose-driven and reflects the characters' social identities, emotions, and interpersonal relationships. The research findings highlight the significance of code switching as a means of effective communication, emphasizing its role in conveying emotions, establishing solidarity, and clarifying speech content. The research methodology employed observation as a data collection method, and the data analysis involved classifying the instances of code switching based on Hoffmann's theory. The results demonstrate that code switching is deliberately used by the characters to navigate diverse social contexts and to adapt their language use based on their communication partners. The characters' linguistic behaviors offer valuable insights into the sociolinguistic dynamics within the novel, enriching the storytelling and enhancing the portrayal of human emotions and connections.